If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ln(x + 5) + ln(x + -2) = 2lnx Reorder the terms: nL(5 + x) + ln(x + -2) = 2lnx (5 * nL + x * nL) + ln(x + -2) = 2lnx (5nL + nxL) + ln(x + -2) = 2lnx Reorder the terms: 5nL + nxL + ln(-2 + x) = 2lnx 5nL + nxL + (-2 * ln + x * ln) = 2lnx 5nL + nxL + (-2ln + lnx) = 2lnx Reorder the terms: -2ln + lnx + 5nL + nxL = 2lnx Solving -2ln + lnx + 5nL + nxL = 2lnx Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-2lnx' to each side of the equation. -2ln + lnx + 5nL + -2lnx + nxL = 2lnx + -2lnx Reorder the terms: -2ln + lnx + -2lnx + 5nL + nxL = 2lnx + -2lnx Combine like terms: lnx + -2lnx = -1lnx -2ln + -1lnx + 5nL + nxL = 2lnx + -2lnx Combine like terms: 2lnx + -2lnx = 0 -2ln + -1lnx + 5nL + nxL = 0 Add '-5nL' to each side of the equation. -2ln + -1lnx + 5nL + -5nL + nxL = 0 + -5nL Combine like terms: 5nL + -5nL = 0 -2ln + -1lnx + 0 + nxL = 0 + -5nL -2ln + -1lnx + nxL = 0 + -5nL Remove the zero: -2ln + -1lnx + nxL = -5nL Add '-1nxL' to each side of the equation. -2ln + -1lnx + nxL + -1nxL = -5nL + -1nxL Combine like terms: nxL + -1nxL = 0 -2ln + -1lnx + 0 = -5nL + -1nxL -2ln + -1lnx = -5nL + -1nxL Reorder the terms: -2ln + -1lnx + 5nL + nxL = -5nL + 5nL + -1nxL + nxL Combine like terms: -5nL + 5nL = 0 -2ln + -1lnx + 5nL + nxL = 0 + -1nxL + nxL -2ln + -1lnx + 5nL + nxL = -1nxL + nxL Combine like terms: -1nxL + nxL = 0 -2ln + -1lnx + 5nL + nxL = 0 Factor out the Greatest Common Factor (GCF), 'n'. n(-2l + -1lx + 5L + xL) = 0Subproblem 1
Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing l to the left, all other terms to the right. Add '-1n' to each side of the equation. n + -1n = 0 + -1n Remove the zero: 0 = -1n Simplifying 0 = -1n The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-2l + -1lx + 5L + xL)' equal to zero and attempt to solve: Simplifying -2l + -1lx + 5L + xL = 0 Reorder the terms: 5L + -2l + -1lx + xL = 0 Solving 5L + -2l + -1lx + xL = 0 Move all terms containing l to the left, all other terms to the right. Add '-5L' to each side of the equation. 5L + -2l + -1lx + -5L + xL = 0 + -5L Reorder the terms: 5L + -5L + -2l + -1lx + xL = 0 + -5L Combine like terms: 5L + -5L = 0 0 + -2l + -1lx + xL = 0 + -5L -2l + -1lx + xL = 0 + -5L Remove the zero: -2l + -1lx + xL = -5L Add '-1xL' to each side of the equation. -2l + -1lx + xL + -1xL = -5L + -1xL Combine like terms: xL + -1xL = 0 -2l + -1lx + 0 = -5L + -1xL -2l + -1lx = -5L + -1xL The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 1824-2x=-2200 | | x+(x+22)+(x-30)=897 | | f(-4)=5(-4)-3 | | y+18=2 | | X-4y=-48 | | y+-6=2 | | 1824+2x=-2200 | | 1824-2x=-2000 | | -176.4+x/5=225 | | 4w^2-49p^2=0 | | (16u^6-12u^4)/4u^3 | | B^3+8=0 | | B^3-64=0 | | 4v^4-1024=0 | | 9s^2+p^2-6sp=0 | | X^3+7x^2-8x-56=0 | | (3+2)(6+8x)=5-6.5(x+3) | | (4x+9y)(4x-9y)= | | 12b^2-11bt-15t^2=0 | | 4x-5a=7 | | 3(9x-24)=3-1(x+5) | | 6x+14-5x=-9x-15+x | | 15x^3-10x+5x=0 | | 24/15-92/5 | | [15-7(x-5y)]+10(7x+y)= | | (0.8+4)(0.8x-4)= | | x+.27x=50 | | 2(x+9)(x-4)=84 | | x*sqrt(x)+5x-22=2 | | (4+8)(3+7x)=50-4.5(x+5) | | 3(4x-34)=4-2(x+5) | | 5x^2-36x-144=0 |